Preparation and Study of the Antibacterial Applications and Oxidative Stress Induction of Copper Maleamate-Functionalized Mesoporous Silica Nanoparticles - Diana Díaz-García; Perla R. Ardiles; Sanjiv Prashar; Antonio Rodríguez-Diéguez; Paulina L. Páez; Santiago Gómez-Ruiz (MDPI AG, 2019)
Mesoporous silica nanoparticles (MSNs) are an interesting class of nanomaterials with potential applications in different therapeutic areas and that have been extensively used as drug carriers in different fields of medicine. The present work is focused on the synthesis of MSNs containing a maleamato ligand (MSN-maleamic) and the subsequent coordination of copper(II) ions (MSN-maleamic-Cu) for the exploration of their potential application as antibacterial agents. The Cu-containing nanomaterials have been characterized by different techniques and the preliminary antibacterial effect of the supported maleamato-copper(II) complexes has been tested against two types of bacteria (Gram positive and Gram negative) in different assays to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). The biological results showed a moderate antibacterial activity against Escherichia coli which motivated a more detailed study of the antibacterial mechanism of action of the synthesized maleamate-containing nanosystems and whose findings showed oxidative stress generation in bacterial cells. All the prepared nanomaterials were also tested as catalysts in the “solvent free” selective oxidation of benzyl alcohol, to observe if there is a potential correlation between the catalytic oxidation capacity of the materials and the observed oxidative stress in bacteria. This may help in the future, for a more accurate rational design of antibacterial nanosystems, based on their observed catalytic oxidation activity.